Intelligent Wheelchair Control Prototype Using Voice Recognition System for Disabled Patients - Nur Zuliyana Mohd Rajdi, Nik; Jothi, Naechitra (International Journal of Engineering and Technology, 2026)
One of the very common disabilities that requires aid is the mobility impairments. Thus, to transport themselves, these individuals will begin to solely depend on an assistive devices, commonly on a traditional wheelchair. In order, to ease the movement of a disabled patient, a technologically advanced wheelchair prototype is developed. The prototype is made up of acrylic plastic and wood and consists of a Voice Recognition System, ultrasonic sensors, LCD display and an emergency brake and it is fabricated in such a way that it is user friendly and safe for the user. The system is programmed in such a way that, the wheelchair prototype moves accordingly to the main five commands which are “Forward”, “Back”, “Left”, “Right” and “Stop”. Besides that, the ultrasonic sensors are embedded at the back and front of the wheelchair prototype, displays alert through the LCD screen which is placed on the hand rest when it senses obstacles. The calculated mean value of all the commands also denotes the accuracy level of the whole wheelchair system which is 95.40%. The value of standard deviation that is obtained through the IBM SPSS Statistics is 2.881 which by means this system is reliable and is accurate.
Keywords: Intelligent wheelchair; Voice recognition system; LCD screen; Ultrasonic sensor; microphone